2007
DOI: 10.1179/174327807x159925
|View full text |Cite
|
Sign up to set email alerts
|

High temperature oxidation behaviour of single crystal superalloys RR3000 and CMSX-4

Abstract: This paper describes the oxidation behaviour of two technologically important nickel based superalloys, RR3000 and CMSX-4, used extensively in gas turbine blade applications. Oxidation tests were conducted in air at 1100uC for equal and extended periods of time, up to 100 h to compare the superalloys characteristic properties. The morphology of oxide growth in the test samples was investigated using metallography, SEM, EDX, X-ray diffraction (XRD) and Cr 3z photoluminescence spectroscopy. The results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 17 publications
4
30
0
3
Order By: Relevance
“…First, the formation of b phase because of Ni-depletion is not unexpected; in fact it is worth pointing out that a study has reported the stabilization of b phase owing to the formation of NiO as a precursor to internal oxidation of CMSX10 at temperatures below 1273 K (1000°C), [19] although the extent of coverage is not as extensive as in our experiments. Second, the de-stabilization of c phase at the surface resulting in a c¢ and TCP phase mixture is also commonly encountered during the aluminisation of Ni aerofoils typically at 1373 K (1100°C).…”
Section: B Sequence Of Microstructure Evolution At the Surfacementioning
confidence: 43%
See 1 more Smart Citation
“…First, the formation of b phase because of Ni-depletion is not unexpected; in fact it is worth pointing out that a study has reported the stabilization of b phase owing to the formation of NiO as a precursor to internal oxidation of CMSX10 at temperatures below 1273 K (1000°C), [19] although the extent of coverage is not as extensive as in our experiments. Second, the de-stabilization of c phase at the surface resulting in a c¢ and TCP phase mixture is also commonly encountered during the aluminisation of Ni aerofoils typically at 1373 K (1100°C).…”
Section: B Sequence Of Microstructure Evolution At the Surfacementioning
confidence: 43%
“…A characteristic EDS spectrum from this region shows that this oxide comprises Ni, Al, and Cr; Figure 3(c). This fine morphology coupled with similar lattice parameters of the spinel phases preclude analyses by diffraction using selective area diffraction mode in the TEM to uniquely identify these mixed oxides; however, mixed oxides of CrTaO 4 , NiAl 2 O 4 , and AlTaO 4 have been reported by Younes et al [19] during oxidation of the third-generation alloy, CMSX10K upto 50 hours. The un-scaled region on the other hand presents a more interesting proposition.…”
Section: B Characterization Of Surface Oxidesmentioning
confidence: 99%
“…Aluminized CMSX-10K formed a region of TCPs beneath the interdiffusion zone (IDZ) and, sporadically around the circumference, a layer of SRZ beneath these TCPs. Other researchers have identified these TCPs as σ-phase [7,9,27]. Aluminized CMSX-10K exposed for 240h at 1100°C only showed one instance of SRZ formation beneath the layer of TCPs.…”
Section: Test Conditionsmentioning
confidence: 94%
“…In both cases, internal fatal crack initiation is obtained but it is noticed that the pre-exposed specimen presents less cracks at the surface compared to the reference one. It seems that static oxidation (i.e., thermal pre-exposition at 1000°C during 100 hours) has formed a non-porous and adherent oxide layer of Al 2 O 3 [55,56] that is more difficult to crack. Oxide layer in the reference specimen is formed in the meantime of the VHCF solicitation.…”
Section: Impact Of Oxidation At R = àmentioning
confidence: 99%
“…More tests at lower stresses (r a = 145 to 150 MPa) should be done in order to exacerbate oxidation damage and enable to observe different rupture modes. Thermal pre-exposition on SX alloys that do not form adherent oxide scales (i.e., MAR-M200+Hf, [57] RR3000 [56] ) could also help to observe the competition between internal and surface initiations.…”
Section: Impact Of Oxidation At R = àmentioning
confidence: 99%